CD4+CD8+ T follicular helper cells regulate humoral immunity in chronic inflammatory lesions - Murayama, Kosuke; Ikegami, Ippei; Kamekura, Ryuta; Sakamoto, Hiroshi; Yanagi, Masahiro; Kamiya, Shiori; Sato, Taiki; Sato, Akinori; Shigehara, Katsunori; Yamamoto, Motohisa; Takahashi, Hiroki; Takano, Ken-ichi; et al. (Frontiers in Immunology, 2022)
T follicular helper (Tfh) cells drive humoral immunity by facilitating B cell responses at the initial and recall phases. Recent studies have indicated the possible involvement of Tfh cells in the process of chronic inflammation. However, the functional role of Tfh cells in persistent immune settings remains unclear. Here, we report that CD4+CD8+ (double-positive, DP; CD3+CD4+CD8+CXCR5hiPD-1hi) Tfh cells, a subset of germinal-center-type Tfh cells, were abundantly present in the fibroinflammatory lesions of patients with immunoglobulin G4-related disease (IgG4-RD). Transcriptome analyses showed that these DP-Tfh cells in the lesions of IgG4-RD preferentially expressed signature genes characteristic of cytotoxic CD8+ T cells, such as Eomes, CRTAM, GPR56, and granzymes, in addition to CD70. Scatter diagram analyses to examine the relationships between tissue-resident lymphocytes and various clinical parameters revealed that the levels of DP-Tfh cells were inversely correlated to the levels of serum IgG4 and local IgG4-expressing (IgG4+) memory B cells (CD19+CD27+IgD-) in patients with IgG4-RD. Cell culture experiments using autologous tonsillar lymphocytes further suggested that DP-Tfh cells possess a poor B-cell helper function and instead regulate memory B cells. Since CD4+ (single positive, SP; CD3+CD4+CD8-CXCR5hiPD-1hi) Tfh cells differentiated into DP-Tfh cells under stimulation with IL-2 and IL-7 as assessed by in vitro experiments, these data imply that SP-Tfh cells are a possible origin of DP-Tfh cells under persistent inflammation. These findings highlight the potential feedback loop mechanism of Tfh cells in immune tolerance under chronic inflammatory conditions. Further studies on DP-Tfh cells may facilitate control of unresolved humoral responses in IgG4-RD pathological inflammation.